Explorasi Fungi Endofit Dari Tanaman Bunahong (Andredera cordifolia (Ten.) Steenis) Sebagai Penghasil Kandidat Senyawa Antibakteri - Ismail Ismail; Megawati Megawati; Nur Fadillah Bakri (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Binahong leaves (Andredera cordifolia (Ten.) Steenis) contain triterpenoid saponins, flavonoids and phenyl propanoid which have antibacterial activity. One source of the antibacterial bioactive compounds is endophytic fungi, are symbiotic microorganisms in plant tissues found in A. cordifolia leaves. This study aims to isolate endophytic fungi from A. cordifolia leaves and their activity against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 83125. The stages in this study included isolation of endophytic fungi, purification, test antagonists, metabolite production and active liquid fermentation tests on test bacteria. The results of this study were 9 endophytic fungi isolates with different characteristics. Of the nine isolates, the best isolates were given in isolation, I8 and I9 isolates with an average inhibitory diameter of 10 mm for Escherichia coli and Staphylococcus aureus.